2018
DOI: 10.1016/j.ajpath.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Peripheral Myelin Protein 22, Reduced Mitotic Potential, and Proteasome Impairment in Dermal Fibroblasts from Charcot-Marie-Tooth Disease Type 1A Patients

Abstract: A common form of hereditary autosomal dominant demyelinating neuropathy known as Charcot-Marie-Tooth disease type 1A (CMT1A) is linked with duplication of the peripheral myelin protein 22 (PMP22) gene. Although studies from animal models have led to better understanding of the pathobiology of these neuropathies, there continues to be a gap in the translation of findings from rodents to humans. Because PMP22 was originally identified in fibroblasts as growth arrest specific gene 3 (gas3) and is expressed broadl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…WT PMP22 is overexpressed in the most common form of CMT disease, CMT1A. This has led to interest in the possibility that misfolded, nondegraded, PMP22 is a source of cytotoxicity contributing to disease etiology (13,23,24,30,31). Here, we examined expression of PMP22 in both transiently transfected model cell lines and in stable cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WT PMP22 is overexpressed in the most common form of CMT disease, CMT1A. This has led to interest in the possibility that misfolded, nondegraded, PMP22 is a source of cytotoxicity contributing to disease etiology (13,23,24,30,31). Here, we examined expression of PMP22 in both transiently transfected model cell lines and in stable cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when PMP22 is reconstituted into lipid bilayers, it is sufficient to induce wrapping of the membranes to produce myelin-like assemblies (12). However, PMP22 has also been implicated in a number of other processes within myelin-producing Schwann cells (1,2,(13)(14)(15)(16). In vitro studies revealed that PMP22 is only modestly stable in detergent micelles, with the native conformation favored over the denatured ensemble by only 1.5 6 0.1 kcal mol 21 (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While mostly known for its linkage to neuropathies, PMP22 is expressed in a variety of cell types, including fibroblasts (Amici et al, 2006; Grossi et al, 1998; Lee et al, 2018; Notterpek et al, 2001). In dermal fibroblasts from CMT1A patients with PMP22 gene duplication, the overproduced PMP22 forms aggregates and activates the autophagy–lysosomal pathway, similarly to Schwann cells from neuropathic mice (Fortun et al, 2006; Lee et al, 2018). Here, we also discovered altered lipid metabolism in CMT1A fibroblasts, as indicated by downregulation of genes linked to sterol synthesis (Figure 2e).…”
Section: Discussionmentioning
confidence: 99%
“…Human skin fibroblasts from four CMT1A patients (GM05148 [P1], GM05167 [P2], GM05146 [P3], and GM05165 [P4]) were purchased from the Coriell Institute (Camden, New Jersey). Skin fibroblasts from nonneuropathic individuals were obtained under an IRB‐approved protocol by Dr Guang‐Bin Xia (Department of Neurology, University of Florida) and were provided to us for the described studies (Lee et al, 2018). All procedures involving the human cells were carried out in compliance with IRB approval.…”
Section: Methodsmentioning
confidence: 99%